To simplify the expression \( 5\sqrt{32} \cdot 2\sqrt{7} \), we can start by rewriting the components we have.
First, multiply the constants and the square roots separately:
\[ 5 \cdot 2 = 10 \]
Next, for the square roots:
\[ \sqrt{32} \cdot \sqrt{7} = \sqrt{32 \cdot 7} \]
Now, calculate \( 32 \cdot 7 \):
\[ 32 \cdot 7 = 224 \]
So, now we have:
\[ 5\sqrt{32} \cdot 2\sqrt{7} = 10\sqrt{224} \]
Next, we simplify \( \sqrt{224} \). We start by factoring \( 224 \):
\[ 224 = 16 \cdot 14 = 16 \cdot (2 \cdot 7) \]
Since \( 16 \) is a perfect square (\( 4^2 \)), we can simplify this:
\[ \sqrt{224} = \sqrt{16 \cdot 14} = \sqrt{16} \cdot \sqrt{14} = 4\sqrt{14} \]
Now, substitute \( \sqrt{224} \) back into our expression:
\[ 10\sqrt{224} = 10 \cdot 4\sqrt{14} = 40\sqrt{14} \]
Thus, the product of the original expression in simplest radical form is:
\[ \boxed{40\sqrt{14}} \]